Experimental Custom-Made Zirconia Abutments for Narrow Implants in Esthetically Demanding Regions: A 5-year Follow-Up - (:unkn) unknown (QUINTESSENCE PUBLISHING CO INC, 2012)
Purpose: This prospective clinical study evaluated an experimental custom-made zirconia abutment with respect to peri-implant hard and soft tissue reaction in narrow implants. Materials and Methods: Patients were treated with prefabricated titanium implants and custom-made zirconia abutments. All-ceramic crowns were fabricated and cemented with resin cement. Clinical parameters such as Plaque Index, Sulcus Bleeding Index, peri-implant probing depth, and radiographic marginal bone loss levels were recorded, along with any biologic and mechanical complications, at baseline and up to 5 years. Results: Twelve patients with missing maxillary lateral incisors treated with a total of 23 implants were evaluated. Thirteen Straumann Narrow Neck Solid Screw implants with a diameter of 3.3 mm and 10 Astra Micro Thread implants with a diameter of 3.5 mm were used. Six patients with 11 implants were treated with custom-made zirconia abutments and prefabricated metal abutments were used in the control group. Implant and abutment success at 5 years was 100%. No abutment fractures occurred. Abutment screw loosening was reported for one restoration at the 1-year recall. Mean marginal bone loss measured 0.21 mm after 5 years of functional loading. Conclusion: Custom-made zirconia abutments offered sufficient stability to support all-ceramic restorations over narrow implants in anterior regions over a 5-year period. The soft and hard tissue reactions to zirconia were favorable. INT J ORAL MAXILLOFAC IMPLANTS 2012;27:1239-1242
Keywords: clinical follow-up; full ceramic crowns; narrow implants; zirconia abutment